2014
DOI: 10.1186/1477-7819-12-335
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer arising within fibroadenoma: collective analysis of case reports in the literature and hints on treatment policy

Abstract: BackgroundBreast cancer arising within a fibroadenoma (BcaFad) is rare; the rate varies from 0.002% to 0.125% in fibroadenoma specimens. Owing to its rarity, the clinicopathologic feature and treatment principle of BcaFad is still not clear. Therefore, the aim of this study was to perform a collective analysis of case reports in the literature to identify the characteristics and optimal treatment for BcaFad.MethodsWe analyzed an aggregated sample of 30 patients with BcaFad from case reports in the literature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 47 publications
2
47
0
1
Order By: Relevance
“…Our unit currently manages presumptive FA that are clinically, radiologically, and pathologically concordant but have a dimension of greater than 30 mm with excision because of the postulated risk of underlying ductal carcinoma in situ (DCIS) or PT, particularly in larger lesions …”
Section: Introductionmentioning
confidence: 99%
“…Our unit currently manages presumptive FA that are clinically, radiologically, and pathologically concordant but have a dimension of greater than 30 mm with excision because of the postulated risk of underlying ductal carcinoma in situ (DCIS) or PT, particularly in larger lesions …”
Section: Introductionmentioning
confidence: 99%
“…The patients with DCIS were treated with breast conservation, however, radiotherapy was given only to two patients based upon clinician's preference. Receptor status was not available for all cases, but where ever positive, hormonal treatment was given [10].…”
Section: Discussionmentioning
confidence: 99%
“…These include invasive as well as in-situ carcinomas. Carcinoma in-situ, both lobular and ductal, was found to be more common in such cases as compared to invasive types [10]. Due to rarity of such cases and unexpected incidental discovery on excision specimens, exact guidelines for further management are not available and management so far is dictated by the malignant component of fibroadenoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a small percentage of fibroadenomas in older women may harbor malignant tumors inside (0.02% to 0.125%) (3). However, the pathology of the surgical specimen revealed that in this case, these two lesions were completely independent, although located very close to each other.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion is frequently associated with other benign pathologies (1, 2), but also has been reported as associated, or concomitant, with malignancies in up to 5% of cases, mainly in older patients (2). In extremely rare cases, these malignancies may be co-located with, or even within a fibroadenoma (0.02%) (3). It has been reported that a high percentage of these concurrent malignancies may be missed (1, 2), and for this reason, radiologists should be very cautious when evaluating fibroadenomas of a given patient within this specific age group.…”
Section: Introductionmentioning
confidence: 99%